(untitled) (Journal of Social Economics Research, 2024)
This research aims to evaluate the impact of Pancasila-based performance on the antifragility level of micro and small enterprises (MSEs) in Indonesia. It specifically figures out the most important aspects of Pancasila-based performance that are linked to antifragility and checks how much using Pancasila values in managing MSEs makes them better at handling problems and disasters. The study used a quantitative research approach. Meanwhile, we collected the data through a questionnaire from 220 MSEs in two cities in East Java, Indonesia, using proportional random sampling. Structural Equation Modelling (SEM) was employed to analyze the data. The finding indicated that Pancasila- based performance positively and significantly influences the antifragility level of MSEs in Indonesia. The research provides a new and original contribution to developing more sustainable, inclusive, and nationally appropriate business strategies for assessing antifragile business performance. Our research provides valuable insights into the significance of enhancing antifragility levels for Indonesia’s MSEs. By measuring antifragile business performance, this study contributes to developing more sustainable, inclusive, and nationally aligned business strategies.